Entrepreneurial Behaviour of Dairy Farmers (Indian Journal of Extension Education, 2017)
The study was conducted in Akola district of Maharashtra state with 100 dairy farmers. The results reveared that two third (67.00%) of dairy farmers belongs to medium entrepreneurial behaviour. Education, land holding, annual income, economic motivation, scientific orientation, and attitude towards dairy farming shows positively and only age found negatively significant relationship with entrepreneurial behaviour. Whereas other variables like experience in dairying, livestock possession and market orientation did not establish significant relationship with their entrepreneurial behaviour.